Effect of neuromuscular deprogramming on quality of life and sleep in patients with temporomandibular dysfunction - Juan Manuel Guizar Mendoza; Claudia Salinas Escoboza; Yuridia Avalos Equihua; Norma Amador Licona; Francisco Espinosa Albo; Salvador Ferrer Tamburini (Editorial Ciencias Médicas, 2022)
Introduction: Neuromuscular deprogramming reduces the main symptoms such as pain by 70 to 90% in patients with temporomandibular dysfunction, but little information is available on the effect on quality of life and sleep. Objective: Determine the effect of neuromuscular deprogramming on quality of life and sleep in patients with temporomandibular dysfunction. Methods: 55 patients with temporomandibular dysfunction were included who were neuromuscularly deprogrammed (29 women and 26 men), with an average age of 34.9 ± 16.5 years. At the beginning and end of neuromuscular deprogramming, surveys were applied to assess the level of chronic pain, perception of quality of life related to oral health, perceived stress, quantity and quality of life, anxiety and depression. Results: In 37 patients (68%) pain was identified on examination, and it was confirmed in the chronic pain survey. The quality of life perception score was correlated with low sleep quality (r = 0.39; p = 0.008); pain score (r = 0.48; p = 0.003); anxiety (r = 0.55; p = 0.003) and depression (r = 0.41; p = 0.006). Neuromuscular deprogramming reduced patient-reported pain levels from 9.9 to 2.9 (p = 0.001), the percentage of patients with poor sleep quality from 60% to 29% (p < 0.0001), the quality of life score from 40.7 to 23.8 (p = 0.03), and perceived stress levels from 22.1 to 19.1 (p = 0.002). Conclusions: In patients with temporomandibular dysfunction, neuromuscular deprogramming reduces the level of pain. It is related to better perception in quality of life, higher quality of sleep and decreases perceived stress.